WATER QUALITY SURVEILLANCE OF THE LOWER GOOSE CREEK WATERSHED IN LOUDOUN COUNTY, VIRGINIA - Hood, Karen (My University, 2021)
Environmental sources of drinking water require routine water quality surveillance to ensure consumer safety; water treatment plants do not protect the water quality of people who swim in streams and rivers, nor do they protect people whose water comes from private wells. While contaminants in water range from natural to man-made, chemical to bacterial, in Loudoun County, Virginia, the main contaminant for waterways is fecal coliform bacteria: Escherichia coli. The Goose Creek and its aquifer provide drinking water to thousands of people via wells, and because it is also a designated Scenic River, the community has the right to freely recreate in the Goose Creek. This Applied Practice Experience consisted of water quality monitoring of the Lower Goose Creek Watershed from December 2020 to January 2021, measuring temperature, nutrients (nitrate, ammonia, orthophosphate), turbidity, dissolved oxygen, conductivity, pH, and the concentration of E. coli at thirteen sampling sites. Because the Goose Creek and some of its tributaries are considered impaired for fecal bacteria, routine monitoring, whether performed by government agencies or local stakeholders, is crucial for assessing and improving water quality.
Keywords: Water quality monitoring; Fecal contimation; Goose Creek; Loudoun County; Escherichia coli